Efek konsentrasi Prekursor Terhadap SIFAT FISIK Film Tipis BASRTIO3 (BST) SRUKRUR MFM DAN MFS yang Ditumbuhkan dengan SPIN COATING - Darvina, Yenni (Sainstek, 2008)
An BST precursor was synthesized by mixing Barium acetate 99,9%, Strontium acetate 99,99% , Titanium isopropoxide 99,999% in 2-methoxyethanol 99,9% and acetic acid glasia 100% at 120oC along 3 hours. The BST precursor concentration were 0.1 M and 0.5 M.  By employing CSD method, the BST precursor was spin coated on p-type Si (100) substrate at 3000 rpm for 30 seconds and pyrolyzed at 130oC at 10 minutes to obtain BST thin films. The BST thin films were annealed for 15 hours at 1000oC. The BST thin films structure were MFM and MFS, characterized their physical properties. It was found that grain size and thickness for the MFM structure at the BST 0,1 M were < 0.3μm and 0.6 μm., And  the BST 0.5 M were 0.5–1.0 μm and 0.9 μm. Grain size and thickness for the MFM structure at the BST 0.1 M were < 0.3μm and 0.6 μm, for BST 0.5M were 0.5–1μm and 0.8 μm .Latis constant 3.936 Ǻ. Composition of BST thin films was  same as BST precursor. Key words : Ferroelektrik, BST, Spin Coating.